Parallel Three-Dimensional Simulation of Ultrasound Imaging - Daoud, M.I.; Lacefield, J.C. (2008 22nd International Symposium on High Performance Computing Systems and Applications, 2008)
Ultrasound imaging simulations provide an important tool in imaging research. However, realistic imaging simulations involve long execution times and require enormous computational resources that exceed the capabilities of serial computers. In this paper, we present a parallel three-dimensional ultrasound simulator that runs on computer clusters and uses a k-space method to compute acoustic propagation. The simulator achieved a mean error value of 0.57%, which demonstrates its numerical accuracy. Parallel computing enhanced the simulator efficiency by enabling imaging simulations with short execution times. For instance, the parallel execution time of a simulated ultrasound image using 20 cluster nodes was 18.61 hours compared to a serial execution time of 357.50 hours.